Fostering positive youth and staff development: Understanding the roles and experiences of the afterschool workforce. Issue 8 (17th August 2020) - Hwang, Sophia H. J.; Watford, J. Alexander; Cappella, Elise; Yates, Miranda; Mui, Stephanie; Nix, Jennifer
Abstract: Informed by strengths‐based perspectives and systems theory of social settings, this mixed‐methods study focuses on the experiences of the afterschool workforce employed by a large, urban community‐based organization. Through directed content analysis of semi‐structured individual and small‐group interviews with afterschool instructors (ASI), this study sheds light on the roles, experiences, challenges, and supports of ASIs. Results demonstrate that ASIs navigate multiple roles in the afterschool setting, acknowledge the challenges of youth and families, experience several sources of professional support through the people and resources in afterschool, and articulate long‐term professional goals related to their current work. In addition, concurrently collected quantitative survey and administrative data about ASIs' overall work experiences and satisfaction are analyzed to examine the extent to which they confirm and complement the qualitative results. Implications for practice and policy are discussed to highlight how these findings may be used to strengthen the youth‐serving workforce in urban communities.